Рентгеноструктурный анализ сплава Ti Grade 4, подвергнутого РКУП-К - Ситдиков, В.Д.; Александров, И.В.; Исламгалиев, Р.К. (Физика и техника высоких давлений, 2012)
В настоящей работе методом рентгеноструктурного анализа исследовано влияние температуры равноканально-углового прессования−«конформ» (РКУП-К) на микроструктуру и механизмы деформации объемных заготовок из Ti Grade 4. Заготовки подвергали РКУП-К с числом проходов от 1 до 8 по маршруту ВС при температурах 200 и 400°C. Установлено, что эволюция микроструктуры и кристаллографической текстуры имеет особенности, зависящие от температуры РКУП-К. Кроме того, обнаружены закономерности формирования преимущественных ориентировок, а также оценена активность тех или иных систем скольжения и двойникования в титановых заготовках в зависимости от числа проходов и температуры РКУП-К. У даній роботі методом рентгеноструктурного аналізу досліджено вплив температури рівноканально-кутового пресування−«конформ» (РККП-К) на мікроструктуру й механізми деформації об’ємних заготовок з Ti Grade 4. Заготовки піддавали РККП-К з числом проходів від 1 до 8 за маршрутом ВС при температурах 200 і 400°C. Встановлено, що еволюція мікроструктури і кристалографічної текстури має особливості, які залежать від температури РККП-К. Крім того, виявлено закономірності формування переважних орієнтувань, а також оцінено активність тих чи інших систем ковзання й двійникування у титанових заготовках в залежності від числа проходів і температури РККП-К. In the present paper, the effect of the temperature of equal channel angular pressing «Conform» (ECAP-Conform) on the microstructure and the deformation mechanisms of bulk Ti Grade 4 billets was investigated by X-ray analysis. The billets were subjected to ECAP-Conform with the number of passes from 1 to 8 via the ВС route at 200 and 400°С. It was established that the evolution of microstructure and crystallographic texture had characteristic features dependent on the ECAP-Conform temperature. In addition, the mechanisms of preferred orientation formation were established. The activity of various slip systems and twinning in titanium billets was estimated depending on the number of passes and the ECAP-Conform temperature. In particular, at a temperature of 200°С, the size of coherent scattering domains decreases, besides, monotonous growth of meansquare microdistortions and dislocation density is observed with the increasing number of passes. At the same temperature, during the first pass of ECAP-Conform, activation of twinning processes that facilitate microstructure refinement occurs. At 400°C the value of mean-square microdistortions as well as the dislocation density in the crystalline lattice after 4 passes start decreasing, which indicates to the processes of dynamic recovery and, feasibly, dynamic recrystallization.